Os fantasmas pornô de Santiago Nazarian e seus adolescentes bizarros - Aileen El-Kadi (Estudos de Literatura Brasileira Contemporânea)
This article analyses the book of short stories Pornofantasma (Record, 2011) by Santiago Nazarian. The focus of this analysis is the connections between the text and the genre of pornography and pop culture, as well as the way the author ques- tions centers and margins of power using the aforementioned genres.